2016
DOI: 10.12816/0027220
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation into the Impact of Change Management on the Wellbeing of Healthcare Workers at Rumailah Hospital in the State of Qatar

Abstract: All organisations will face change at some point if they want to maintain a competitive edge. It has been suggested that change affects employee wellbeing and engagement which could impact on organisational performance. In recent years research has been conducted globally regarding change management and how it affects the employee and ultimately organisational performance. Currently no research is available in Qatar regarding change management, employee wellbeing and engagement and the effect on the organisati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…In addition, Westgaard and Winkel [25] found that changes that are supported by the active participation of employees or employees, clear information, two-way communication, leadership and organizational support, as well as being driven by continuous efforts to promote employee welfare, will encourage an increase in employee or employee performance. even better [26].…”
Section: Discussionmentioning
confidence: 95%
“…In addition, Westgaard and Winkel [25] found that changes that are supported by the active participation of employees or employees, clear information, two-way communication, leadership and organizational support, as well as being driven by continuous efforts to promote employee welfare, will encourage an increase in employee or employee performance. even better [26].…”
Section: Discussionmentioning
confidence: 95%
“…Getting tasks/activities done effectively and efficiently by, with and through people is management. Drucker (2011) as cited inSchutte-Lyth et al (2016) sees management as being able to use all resources, including human resources effectively, to realize strategic goals by implementing a systematic and creative plan. Managers should strive to be good leaders Nzioka, 2012).…”
mentioning
confidence: 99%